Anthocyanin Activity of Red Dragon Fruit (Hylocereus polyrhizus) Peel as Immunostimulan in the Covid-19 Pandemic Era - Fitriyani Fitriyani; Lisa Aulia Zahra; Istifadah Istifadah (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2022)
Background: Coronavirus disease (Covid-19) are generally self-limiting diseases that rely on immune power. Certain food nutrients can be essential in maintaining health and boosting the immune system. One of the nutrients that can maintain and boost the immune system is a flavonoid, which is found in the peel of the red dragon fruit (Hylocereus polyrhizus). The red dragon fruit peel is rich in polyphenols and anthocyanins-flavonoid, which are sources of antioxidants. Dragon fruit peel waste is developed and processed into innovative food in the form of “bakpao” as a source of nutrition and adds to the public's attractiveness, which is then labelled the product